Perceraian Orang Tua dan Pengaruhnya terhadap Persepsi Anak tentang Pernikahan dan Kehidupan Keluarga: Studi Kasus di Desa Pengasinan, Bekasi - Siti Fatimah Azzahra; Agus Supriyanto; Musyaffa Amin Ash-Shabah; Suprihatin (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2026)
This study examines how parental divorce shapes children’s views on marriage and family life in Pengasinan Village, Bekasi. Previous studies on parental divorce have generally focused more on the psychological impact and emotional adjustment of children, while attention to how children interpret marriage, long-term commitment, and future family relationships after experiencing parental divorce remains limited. This study employs a qualitative case study approach through in-depth interviews with selected participants from divorced families. Data were analyzed using thematic analysis and interpreted through the perspective of maqāṣid al-syarī‘ah, specifically hifẓ an-nafs and hifẓ an-nasl. The results indicate that parental divorce influences children’s views on marriage by fostering emotional insecurity, fear of conflict, distrust of long-term commitment, and a cautious attitude toward interpersonal relationships. Experiences of family conflict, emotional distance, and changes in family structure contribute to the formation of children’s negative views regarding marital stability and emotional closeness. This study also found that emotional support, social environment, coping strategies, and religious values play a significant role in shaping children’s resilience and readiness to build a family in the future.